Respon Petani Lorong Pelaksana Urban Farming Terhadap Pengembangan Agribisnis Cabai Di Kota Makassar - Isdialah Isdialah (Pusat Riset dan Inovasi Nasional, 2023)
Urban farming in Makassar City is one of the government programs called Lorong Garden where the people who carry out this activity are called alley farmers and they do chili cultivation to fulfill their daily needs and also as additional income. This study aims to identify the response of alley farmers to the implementation of chilli urban farming. This research was conducted in Makassar City, South Sulawesi Province. The selection of this location uses a purposive sampling technique based on the consideration that all districts in Makassar are the executors of this urban farming program. Respondents in this study are urban farming actors, namely the aisle farmers. To find out the description of the implementation of urban farming in Makassar, a qualitative descriptive analysis was used to see the activities of the executors of urban farming starting from land preparation, planting, maintenance, harvesting to marketing. Data collection was carried out through semi-structured interviews with respondents in the field in order to provide the information needed. It was concluded that the response given by the urban farming aisle farmers was very good at this activity, it was seen that the community was active in training, increasing household income, killing healthy and nutritious community food, improving the environment and the potential for chili agribusiness development.